Effect of Incessant Strike Actions on the Academic Performance of University of Ibadan Medical Students - Uzendu Ezinne; Babatunde Ademusire; Chibuzo Makata; Nnaemeka Ozonta; Kenechukwu Okeke; Hope Abu; Immanuella Yisa; Tobi Ogunleye; Toluwanimi Adeyanju; Oluwasomidoyin Bello (Pan-African Journal of Education and Social Sciences)
A strike is an organized work stoppage by employees. It has become an adopted lingua franca for the Academic Staff Union of Universities (ASUU) to effectively communicate their demands in Nigeria. Using a cross-sectional study design, we investigated the impact of strike actions on the academic performance of fifth- and sixth-year medical students at the University of Ibadan, Nigeria. A total of 242 medical students participated, and 119 (49.2%) had experienced strike actions at least five times during their studies. Most students, 196 (81.0%), believed that strikes affected their motivation to study, while 38 (15.7%) had a re-sit in their examination. The strikes significantly affected students’ motivation (OR=3.10; 95% CI=1.113-8.620), long-term retention of medical knowledge (OR=0.46; 95% CI=0.257-0.815) and having a re-sit among those above 25 years old (OR=1.17; 95% CI=1.025-1.327) and male students (OR=4.91; 95% CI=1.618-14.894). Incessant strikes decrease medical students’ long-term memory of medical knowledge and motivation for studying and increases the tendency to have a re-sit. We therefore suggest that ASUU consider alternative grievance strategies to prevent these negative consequences on future physicians’ education and professional competence.